Various Restoration Processes of Periodicals with Regard to Experiences of the Bibliotheque Nationale, Paris - Delaunay, Else (Cadernos BAD, 1991)
Various Restoration Processes of Periodicals with Regard to Experiences of the Bibliotheque Nationale, Paris